2017
DOI: 10.21037/atm.2017.03.68
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical atherosclerosis in patients with inflammatory bowel diseases: a case-control study

Abstract: Background: An independent role of chronic inflammation in the atherosclerotic process in patients with inflammatory bowel diseases (IBD) has been suggested, but data are still contentious. We assessed preclinical atherosclerosis in the IBD patients without traditional risk factors. Methods:In this case-control study we assessed the early atherosclerotic alterations by carotid artery intima-media thickness (CIMT) measurement in IBD patients and matched controls. The normal CIMT values were ≤0.9 mm; moderate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In 23 studies with 1367 IBD patients and 1127 matched controls [ 13 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], cIMT was found to be significantly increased in patients with IBD compared with the matched controls (Cohen’s d: 0.63; 95% CI: 0.34, 0.93; p < 0.01, Figure 2 A). However, the heterogeneity among the studies was significant (I 2 = 91.84%; p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 23 studies with 1367 IBD patients and 1127 matched controls [ 13 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], cIMT was found to be significantly increased in patients with IBD compared with the matched controls (Cohen’s d: 0.63; 95% CI: 0.34, 0.93; p < 0.01, Figure 2 A). However, the heterogeneity among the studies was significant (I 2 = 91.84%; p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Table S1: Participant characteristics of included studies; Table S2: Measures of disease activity and data on treatment in patients with IBD of included studies; Table S3: Outcomes of patients with IBD and Controls in included studies; Figure S1: Funnel plot of publication bias of cIMT, cfPWV, and FMD. References [ 13 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…It has been postulated that earlier age of diagnosis leads to longer exposure to inflammatory dysregulation with an increased risk of ACS among younger patients. [32][33][34] We further explored this relationship by only including risk estimates adjusted for traditional cardiovascular risk factors in multivariable models as well as performing subgroup analysis based on follow-up duration. Our analysis found that patients with longer duration of follow-up (greater than 5 years) was not associated with a greater risk of ACS than patients with shorter duration.…”
Section: Discussionmentioning
confidence: 99%